From Awareness to Advocacy: A Conceptual Framework on Green Marketing and Consumer Participation - Abdullah, Muhamad Al Faruq; Usep Suhud (International Journal of Advanced Multidisciplinary, 2025)
As environmental sustainability becomes a core concern for consumers, brands must rethink their green marketing strategies not merely to drive purchase, but to cultivate deeper consumer participation and advocacy. This conceptual paper proposes an integrated framework that maps the consumer journey from green brand awareness to active advocacy. Drawing upon the Theory of Planned Behavior and the Stimulus-Organism-Response (S-O-R) model, the framework highlights key psychological constructs—such as attitude, subjective norms, and perceived behavioral control—and links them to digital engagement as a catalyst for consumer mobilization. Unlike traditional models that conclude at purchase behavior, this framework advances the discussion toward post-purchase advocacy, examining how digital platforms empower consumers to promote, co-create, and influence sustainable practices. The model offers theoretical advancements and practical insights for brands aiming to foster long-term environmental engagement through marketing strategies that activate participation beyond transactional touchpoints.